CHANGE OF CORAL REEFS CONDITION IN PARK TOURISM (TWP) PIEH ISLAND WEST SUMATERA PROVINCE - Mulyadi, Hari; Samiaji, Joko; Elizal, Elizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT                This research was conducted in July 2017 at Pieh Island Conservation Area of Pieh Water Park of West Sumatera Province. This study aims to determine the condition of coral reefs in the waters of Pieh Island and to determine the changes in the condition of coral reefs in Pieh Island. The method used was survey method using Underwater Photograph Transect (UPT), consisting of 3 stations where each station was divided into 2 depth ie at depth of 5 meter and 10 meter.               The type of coral reefs on Pieh Island was in the group of fringing reef. The forms of coral growth found in the study area were Acropora branching (ACB), Acropora digitate (ACD), Acropora encrusting (ACE), Acropora submssive (ACS), Acropora tabulate (ACT), Coral encrusting (CE), Coral massive (CM ) Coral Foliose (CF) and Coral Submassive (CS). Condition of coral reefs at Pieh Island at 5 meter depth was heavily devastated with the percentage of 22.80%, while percentage of coral cover at 10 meter depth was 58.67% categorized coral cover good. Keywords: Pieh Island, Coral Reef, Underwater Photograph Transect